Air concentrating nozzles: a promising option for wind turbines. (19th December 2005) - Shikha, S.; Bhatti, T.S.; Kothari, D.P.
Although the use of wind turbines has become necessary in many parts of the world, the actual developments in wind turbines do not concern countries where the average wind speeds are low. The paper introduces a new vertical axis wind rotor using a convergent nozzle for low wind speed areas. This paper brings a detailed theoretical and practical study of air concentrating nozzle and the optimum nozzle dimensions have been analysed in detail. A research programme involving wind tunnel tests of five different nozzle models has also been conducted. The length and the outlet area of the nozzle were changed periodically to see their effect on the increase of wind speed. The variation of the output speed with different values of input wind speed, different input areas of nozzle and different lengths of nozzle placed at different distances from the wind tunnel have been outlined in the paper. Results of additional study of the new rotor's performance characteristics using concentrating nozzles have also been outlined.